First Concurrent Observations of NO2 and CO2 From Power Plant Plumes by Airborne Remote Sensing. Issue 14 (20th July 2021) - Fujinawa, Tamaki; Kuze, Akihiko; Suto, Hiroshi; Shiomi, Kei; Kanaya, Yugo; Kawashima, Takahiro; Kataoka, Fumie; Mori, Shigetaka; Eskes, Henk; Tanimoto, Hiroshi
Abstract: Combined NO2 and CO2 observations have the potential to constrain the identification of the locations and strength of urban CO2 emissions, in particular, point sources such as power plants. We report the first results of airborne spectroscopic NO2 and CO2 observations over an urban area in Japan in February 2018. Inversed emission rates of two stacks of the coal‐fired power plant for CO2 showed relatively good agreement with those estimated by a bottom‐up inventory—the Regional Emission inventory in ASia (REAS) v3.1—within −7% to 40% because the plume shapes were well identified due to constraint by NO2 measurements. The estimated NOx emission rates showed discrepancies more than 80% with those estimated by the REAS v3.1, mainly due to the uncertainties in activity data and emission factors, or in the greatly varying NO/NO2 ratios in fresh plumes, which warrant further investigations when estimating NOx emissions from satellite NO2 observations on km‐scales. Plain Language Summary: Burning of fossil fuels at high temperatures constitutes a major anthropogenic source of nitrogen oxides (NOx ) and carbon dioxide (CO2 ). While CO2 stays in the atmosphere for hundreds of years, thereby being a well‐mixed gas, NO2 has a much shorter lifetime of only a few hours. This substantial difference in lifetime between NO2 and CO2 means that concurrent NO2 and CO2 observations obtained by the same platform can be used to identify the locations and strength of CO2 emissions from point sources such as power plants. In February 2018, for the first time, we obtained concurrent airborne spectroscopic NO2 and CO2 observations over an urban area, to demonstrate the traceability of NO2 to CO2 . The plumes of co‐emitted NO2 and CO2 were derived from measured spectra. The plumes of NO2 and CO2 co‐emitted from the stacks of power plants were well identified owing to constraint by NO2 . Uncertainties of inversed emission rates were statistically derived. For CO2, the results were within 40% in agreement with a bottom‐up emission inventory known as REAS v3.1. For NOx, however, a disagreement of 80% was identified, likely due to the uncertainties of the inventory data or in the NOx partitioning in fresh plumes. Key Points: Concurrent observations of NO2 and CO2 in fresh plumes from a large single point source using airborne spectrometers were reported Columnar enhancements of NO2 and CO2 due to power plant emissions were up to 3.8 × 10 16 molec.cm −2 and 75 ppm, respectively Plume shapes of CO2 emitted from power plants were well identified and constrained by NO2 plume shapes